EFEKTIVITAS PENGGUNAAN APLIKASI PENDAFTARAN DAN PEMBELAJARAN BAHASA INGGRIS BERBASIS ANDROID DI EFS - Muhadzdzib, Muhammad Syafiq; Rahmawati, Yunianita; Busono, Suhendro (Politeknik Bisnis Indonesia, 2023)
The development of software technology is currently very fast and significant, especially in information systems, and one of them is the development of learning application technologies for mobile devices. In time, application technologies can also be learned through mobile phones. Android is an operating system that supports learning from mobile applications. English For Skill (EFS) is one of the English learning courses in Kediri. Almost a dozen or even hundreds of students do English to learn skills and are fluent in English, but the learning system used in the institution still uses a paper text system and the reason is that there are many books scattered and useless books. So we need a learning and registration app that is accessible to students anytime, anywhere. Based on this, this study aims to create an Android based registration and learning application for English For Skill institutions. This registration and learning application uses the software development lifecycle methodology. The steps in this methodology include analysis, design, implementation, testing and maintenance. The resulting registration and learning application should make it easier for institutions to implement the registration and learning systems that have been implemented.